Come fly the world : the jet-age story of the women of Pan Am - Cooke, Julia (Houghton Mifflin Harcourt, 2021)
"A lively, unexpected portrait of the jet-age stewardesses serving on iconic Pan Am airways between 1966 and 1975"--